PREVALENCE AND RISK FACTOR OF STONGYLOIDOSIS IN BEEF CATTLE IN KASIMAN SUBDISTRICT, BOJONEGORO - Ridwan, Yusuf; Satrija, Fadjar; Winarso, Aji (Universitas Syiah Kuala, 2019)
A pair of cross-sectional studies was conducted to determine prevalence and risk factors of Strongyloides spp. (threadworm) infections in beef cattle in Kasiman Subdistrict, the Regency of Bojonegoro. A total of 263 and 270 of local beef cattle with various age were selected for faecal sample during dry season (August-October) and wet season (February-March), respectively. Feces were processed for counting the number of eggs per gram feces (EPG) using McMaster method. The prevalence of strongyloidosis was 4.56% and 7.04% in the dry season and the rainy season, respectively. The factors that associated with prevalence and intensity infection were age and sex of cattle. During the dry season and the rainy season, the calf and weaner group (1 year) was more susceptible for Strongyloides infection than cattle with older age and showed higher intensity of infection (based on EPG values). The bulls showed a higher risk and intensity of infection than cows.